Microplastics in the digestive organs of little egret (Egretta garzetta) in Tanjung Rejo Village, Deli Serdang District, North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Jumilawaty E, Harahap MA, Basyuni M, Slamet B. 2025. Microplastics in the digestive organs of little egret (Egretta garzetta) in Tanjung Rejo Village, Deli Serdang District, North Sumatra, Indonesia. Biodiversitas 26: 2460-2466. Microplastics, derived from the degradation of plastic waste measuring
Keywords: Aquatic avifauna, environmental contamination, gastrointestinal tract, microscopical examination, polymer debris